2016
DOI: 10.3171/2015.6.spine141250
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of the craniocervical junction relative to the hard palate: a lifetime story

Abstract: OBJECT Endoscopic approaches to the anterior craniocervical junction are increasing in frequency. Choice of oral versus endoscopic endonasal approach to the odontoid often depends on the relationship of the C1–2 complex to the hard palate. However, it is not known how this relevant anatomy changes with age. We hypothesize that there is a dynamic relationship of C-2 and the hard palate, which changes with age, and potentially affects the choice of surgical approach. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Indeed, Mallory et al reported that the craniocervical junction undergoes dynamic position changes during a person's lifetime. 13 The position of the craniocervical junction, measured as the distance between the McGregor line and the inferior C-2 endplate, increases through the 4th and 5th decades of life and is followed by settling. Unfortunately, measuring the position of the craniocervical junction based on the McGregor line was impossible in our case because the caudal part of the occiput, which is used as a reference for locating the line, was lost during foramen magnum decompression.…”
Section: Fig 4 a And Bmentioning
confidence: 99%
“…Indeed, Mallory et al reported that the craniocervical junction undergoes dynamic position changes during a person's lifetime. 13 The position of the craniocervical junction, measured as the distance between the McGregor line and the inferior C-2 endplate, increases through the 4th and 5th decades of life and is followed by settling. Unfortunately, measuring the position of the craniocervical junction based on the McGregor line was impossible in our case because the caudal part of the occiput, which is used as a reference for locating the line, was lost during foramen magnum decompression.…”
Section: Fig 4 a And Bmentioning
confidence: 99%
“…T-EMG is an IONM technique that involves electrical stimulation of nerve roots using a hand-held probe, and the measurement of compound muscle action potentials (CMAPs) from muscles innervated by these roots [4]. It is highly useful for surgeries involving the lower abdominal and pelvic areas which put bowel and bladder functions at high risk of neural damage [5].…”
Section: Introductionmentioning
confidence: 99%